2015
DOI: 10.1016/j.bjane.2013.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic efficacy of the ultrasound-guided blockade of the transversus abdominis plane – a systematic review

Abstract: The transverse abdominal plan blockades have been shown to be an effective technique in colorectal surgery, cesarean section, cholecystectomy, hysterectomy, appendectomy, donor nephrectomy, retropubic prostatectomy, and bariatric surgery. However, the data found in randomized clinical trial are not conclusive, and as a result, it is necessary to develop new and well designed randomized clinical trial, with enough statistical power to compare different approaches, drugs, doses, and volumes for the same interven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 57 publications
2
29
0
Order By: Relevance
“…Bjerregaard et al reported that the TAP block is an effective method of analgesia following abdominal surgery, as part of multimodal analgesic regimens. The authors found lower pain scores at rest and during mobilization (coughing) at 4,8,12,20,26, and 36 hours after the operation. Additionally, the cumulative consumption of intravenous morphine was lower in the first 48 hours postoperatively in patients with abdominal transverse plane block [23].…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…Bjerregaard et al reported that the TAP block is an effective method of analgesia following abdominal surgery, as part of multimodal analgesic regimens. The authors found lower pain scores at rest and during mobilization (coughing) at 4,8,12,20,26, and 36 hours after the operation. Additionally, the cumulative consumption of intravenous morphine was lower in the first 48 hours postoperatively in patients with abdominal transverse plane block [23].…”
Section: Discussionmentioning
confidence: 87%
“…[19][20][21][22]. McDonnell et al, in a randomized doubleblind study, evaluated the analgesic efficacy of transverse abdominal plane block in patients after abdominal surgery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because of the difficulty of anatomical references in obese patients, ultrasound guided (USG) TAP blocks have been reevaluated [10]. Sinha et al [11] demonstrated improvement of three different variables: lower pain scores in VAS, less need for opioids (Tramadol) therefore allowing for less sedation and early ambulation.…”
Section: Transverses Abdominis Plane Block (Tap) Blockmentioning
confidence: 99%